Project-Based Learning in Analytic Geometry Courses to Support Student’s Mathematic Communication Skill - Wulandari, Yunita Oktavia; Yuniarto, Eko; Octavianti, Cynthia Tri (Universitas Islam Negeri Antasari Banjarmasin, South Kalimantan, Indonesia, 2023)
This research aims to design project-based learning in analytical geometry learning to develop students' mathematical communication skills. This research is motivated by the reluctance of the majority of students to express their opinions during class learning. Project-based learning was chosen because it has process-centered, problem-focused characteristics, integrating the concepts of several components of knowledge, disciplines, and field experience. Some exciting learning video designs on parabolas, ellipses, and hyperbolas were found in the findings of this project. Definitions, methods for analytically characterizing parabolas, ellipses, and hyperbolas, as well as example problems and exercises, are all included in the learning videos. The video showed that students could audio-visually express mathematical ideas about conic slices, presenting in algebraic form or using mathematical symbols. Through this project assignment, students can also develop their digital literacy skills.